Compound-split drivetrains for rotorcraft - Paschinger, P.; Amri, H.; Hartenthaler, K.; Weigand, M. (My University, 2017)
The investigation presented in this paper is part of the international research project VARI-SPEED with the aim to invent a speed-variable drivetrain for different rotorcraft configurations to reduce the required propulsion power, which enables a modern and ecologically efficient aviation. The research is focused on drivetrain technologies for rotorcraft to enable a variable rotor speed. In the first part known variable transmission drivetrain technologies were listed. Evaluation parameters for usage of transmissions in rotorcraft were defined and rated with a utility analysis. The listed drivetrain technologies were evaluated according to their ability to fulfil the requirements of the evaluation parameters. It could be shown that continuously variable transmission power split gearboxes have the highest potential to be used in rotorcraft. Mechanical discrete variable transmission gearboxes may also have a potential to be used in rotorcraft but the shifting process could be a problem. In the next step the three power split gearbox configurations – Input Split, Output Split and Compound Split – were an¬alysed according to their power split behaviour at different transmission ratios. The more power is transferred via the mechanical path the higher the efficiency is and the lower the additional mass is. In the investigation a spread of two was assumed. This results in a maximum power flow via the variator path of 66 % for the Output Split, of 40 % for the Input Split and of 17 % for the Compound Split. To take safety aspects and specification regulations into account, a FMEA for the Compound Split was carried out. It could be shown, that with additional measures there won’t be an additional risk in the drivetrain for a rotorcraft using a Compound Split. The findings of this research show the direction of further investigation on transmission variable gearboxes for rotorcraft. Knowing that Compound Split offers the highest potential different types can be developed and evaluated for usage.